2022
DOI: 10.3347/kjp.2022.60.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Glucose-6-Phosphate Dehydrogenase (G6PD) Deficiency among Malaria Patients in Southern Thailand: 8 Years Retrospective Study

Abstract: Erythrocytes deficient in glucose-6-phosphate dehydrogenase (G6PD) is more susceptible to oxidative damage from free radical derived compounds. The hemolysis triggered by oxidative agents such as primaquine (PQ) is used for the radical treatment of hypnozoites of P. vivax. Testing of G6PD screening before malaria treatment is not a common practice in Thailand, which poses patients at risk of hemolysis. This retrospective study aimed to investigate the prevalence of G6PD in malaria patients who live in Southern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 45 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…G6PD Kaiping, G6PD Vanua Lava, and G6PD Coimbra were Class B variants and potentially susceptible to 8-aminoquinoline hemolytic toxicity [ 45 , 46 ]. G6PD Mahidol was previously reported to be the most common variant in southern Thailand, and it is also commonly found in Malaysia [ 29 , 31 , 47 , 48 ]. However, G6PD Viangchan and G6PD Mediterranean (Class B variants), the other two most common variants among Malays, were not found in our study [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…G6PD Kaiping, G6PD Vanua Lava, and G6PD Coimbra were Class B variants and potentially susceptible to 8-aminoquinoline hemolytic toxicity [ 45 , 46 ]. G6PD Mahidol was previously reported to be the most common variant in southern Thailand, and it is also commonly found in Malaysia [ 29 , 31 , 47 , 48 ]. However, G6PD Viangchan and G6PD Mediterranean (Class B variants), the other two most common variants among Malays, were not found in our study [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 88-vivax patients from Yala province, the mutation frequency was 5.68% and Class B G6PD variants with a risk of mild to severe drug-induced hemolysis were identified. A previous study with a larger sample size reported G6PD deficiency in 1.1% (6/562) of the 562 malaria patients in Yala province [ 29 ]. Using DiaplexC G6PD genotyping kit (Asian type), they identified G6PD Mahidol and G6PD Viangchan with the frequency of 0.5% and 0.4% in vivax malaria patients (n = 545).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of G6PD deficiency and G6PD variants has been reported in the southern Thai population. However, those reports recruited the samples from one province and five provinces with a high prevalence of malaria ( Pattaranggoon & Yimtiang, 2014 , Khammanee et al, 2022 ) with a retrospective study. The samples from all provinces located in southern Thailand were collected in a cross-sectional study in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In persons with G6PD deficiency, both drugs, PQ and TQ can hemolyze red blood cells, resulting in anemia [ 98 ]. PQ's hemolytic activity has long been thought to be caused by intraerythrocytic oxidative stress mediated by redox-active metabolites rather than the parent drug.…”
Section: Control Challengesmentioning
confidence: 99%